2003
DOI: 10.1007/s00170-003-1544-y
|View full text |Cite
|
Sign up to set email alerts
|

A study on the stress and nonuniformity of the wafer surface for the chemical-mechanical polishing process

Abstract: In this paper, a two-dimensional axisymmetric quasic-static model for the chemical-mechanical polishing process (CMP) was established. Based on the principle of minimum total potential energy, a finite element model for CMP was thus established. In this model, the four-layer structures including the wafer carrier, the carrier film, the wafer and the pad are involved. The von Mises stress distributions on the wafer surface were analysed, and the effects of characteristics of the pad and the carrier film and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…Finally, it increases drastically and peaks significantly at the edge as shown in Fig. 6(a) and (b) [9]. This result is similar to that of [6].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, it increases drastically and peaks significantly at the edge as shown in Fig. 6(a) and (b) [9]. This result is similar to that of [6].…”
Section: Resultssupporting
confidence: 91%
“…Lin and Lo [9] showed that the elastic modulus and thickness of pad and carrier load would significantly affect the von Mises stress and non-uniformity on wafer surface, but those of the film did not affect a lot. Therefore, the CMP process parameters are selected by varying the carrier load in the range of 0.03448-0.10345 MPa, the pad's elastic modulus in the range of 1.1448-3.4345 MPa and the pad's thickness in the range of 0.6985-2.0955 mm.…”
Section: Problem Statementmentioning
confidence: 98%
See 1 more Smart Citation
“…[1][2][3][4] The CMP is based on a rotating table, a polishing head and a suspension pad, where the surface of the wafer moves across the pad, under pressure, in the presence of slurry abrasive. The mechanical movement and the downward force are applied to the wafer by the machine.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the axial stress and strain are the dominant factors of the von Mises stress distribution on the wafer surface and the wafer deformation, and its profile is similar to Srinivasa-Murthy et al (1997), i.e., the curve peaks at the edge. Lin and Lo (2003) investigated further the effects of characteristics of the pad, carrier film, and carrier load on the von Mises stress and NU on the wafer surface by using the developed finite element model. They found that the carrier load, pad's modulus of elasticity, and thickness of pad would significantly affect the von Mises stress and NU, but those of the film did not have much effect.…”
Section: Introductionmentioning
confidence: 99%